Isolation and Identification of Spoilage Yeasts in Wine Samples by MALDI-TOF MS Biotyper - Attila Kántor (Scientific Papers Animal Science and Biotechnologies, 2015)
Many genera and species of microorganisms can be found in grape musts and wines at various times during the winemaking process. For instance, Saccharomyces, Brettanomyces, and Pediococcus can be found together in wine. There are many species of yeast involved in wine spoilage during storage. Aim of this study was to isolate the spoilage yeasts from wine samples with using special selective agar media and identified on species level by Matrix-Assisted Laser Desorption/Ionization-Time of Fly Mass Spectrometry (MALDI-TOF MS). Six red wines used in this study. We identified 10 yeast species from 152 isolates. The most common species in wine samples was Saccharomyces cerevisiae. We also identified four Candida species, two Zygosaccharomyces species and one species from genus Rhodotorula, Saccharomycodes and Dekkera.